1973
DOI: 10.1021/i260048a011
|View full text |Cite
|
Sign up to set email alerts
|

A Rate Approach to Design of Perforated-Plate Extraction Columns

Abstract: An attempt is made to integrate some of the many and diverse studies on droplet phenomena into a coherent design procedure for perforated-plate liquid extraction columns. Equations describing mass transfer during droplet formation, rise, and coalescence, and incorporating relevant hydrodynamics, are used to locate a pseudoequilibrium curve. This curve is used in place of the true equilibrium relationship when stepping off the necessary number of actual stages between the pseudoequilibrium and operating curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…The design procedure recently published by Skelland and Conger (1973) for liquid-liquid extraction in perforated plate columns uses a phenomenological approach, and its continued development should be useful both for the design of new processes and for predicting the results of modifying the operation of existing equipment.…”
Section: Conclusion and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The design procedure recently published by Skelland and Conger (1973) for liquid-liquid extraction in perforated plate columns uses a phenomenological approach, and its continued development should be useful both for the design of new processes and for predicting the results of modifying the operation of existing equipment.…”
Section: Conclusion and Significancementioning
confidence: 99%
“…From this collection, Skelland and Conger (1973) used the following in their design procedure for nonjetting conditions.…”
Section: Mass Transfer During Drop Formation Free Fall and Coalescencementioning
confidence: 99%
“…The work should aid in applying the design procedure for perforated plate extraction columns presented by Skelland and Conger ( 1973) to commercial systems, where dispersed phase holdups are quite high. 'Present address: Amoco Oil Company, 2401 5th Avenue South, Texas City, Texas 77590, USA.…”
mentioning
confidence: 99%
“…It has been observed that Skelland and Conger (1973) (for k ij of stagnant drops), Wesselingh and Krishna (1990) (for D ij ), and Siddiqi and Lucas (1986) (for D ij 0 ) as suggested by Sanpui and Khanna (2002) are the best combination for the TAW and MAW systems.…”
Section: Superscripts and Subscriptsmentioning
confidence: 99%
“…(B5) Skelland and Conger (1973) proposed the expressions for slip velocity, formation, and rise time as given below: Slip velocity:…”
Section: Superscripts and Subscriptsmentioning
confidence: 99%